2021
DOI: 10.3390/su13158425
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Virtual Reality Software to Promote the Learning of Students with Dyslexia

Abstract: The research conducted is part of the European project Erasmus+ FORDYSVAR, whose main objective is to contribute to the educational inclusion of students with dyslexia, aged between 10 and 16 years old, through the use of technology, specifically virtual reality (VR), to improve the access, participation, and educational achievement of students with this learning difficulty. This is a qualitative and interpretative study with a descriptive character. The objective of this work is to design a VR application tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…In such a way that the analysis for our project is a fundamental part to know the users and give a solution, according to the author [15] the mobile application attracts the attention of the child with dyslexia since it is a training for them, in such a way that in our project is dedicated to the mobile application with augmented reality, also that the author of the project is dedicated to the mobile application with augmented reality. The mobile application draws the attention of the child with dyslexia as it is a training for them, so that in our project is dedicated to the mobile application with augmented reality, as well as that the author [17] indicates the usefulness of the mobile application, because nowadays people have a mobile device, so it is very useful for children to learn or improve dyslexia at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a way that the analysis for our project is a fundamental part to know the users and give a solution, according to the author [15] the mobile application attracts the attention of the child with dyslexia since it is a training for them, in such a way that in our project is dedicated to the mobile application with augmented reality, also that the author of the project is dedicated to the mobile application with augmented reality. The mobile application draws the attention of the child with dyslexia as it is a training for them, so that in our project is dedicated to the mobile application with augmented reality, as well as that the author [17] indicates the usefulness of the mobile application, because nowadays people have a mobile device, so it is very useful for children to learn or improve dyslexia at home.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we are sure that the use of augmented reality for dyslexic children helps them to interact with technology, drawing their attention and facilitating specialists to de-understand their behavior with reading comprehension [15] [16]. Making a variety of innovative proposals for users with dyslexia is a great contribution, since the simulation allows those involved to give their respective opinions on the proposal until bringing it to its development, therefore the design of augmented reality in education contributes to student learning to such an extent that it fulfills its objective of including students with dyslexia and improving their participation with the use of these technologies [17] [18]. Augmented reality is one of the most effective techniques for education and entertainment, as well as to give motivation to their students in their learning process, so this research shows that students with dyslexia use the application with augmented reality to follow the letters in such a way that they are pronounced by the students [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11], [12], [13], [14], [15] Movil These articles denoted the importance of implementing a mobile application, being a practical environment and widely used by most students. Where easy accessibility helped to improve cognition and autonomous learning.…”
Section: Efficiency In Its Implementation Referencesmentioning
confidence: 99%
“…[37], [38], [39], [40] Likewise, social networks can be used as a learning platform, for example, the use of a social network such as Facebook Gaming (FBG) was a change very accepted by students since it is not only a known platform but also allows live interaction, changing the approach to the use of social networks [28], similarly, mobile technology helped to enhance academic performance in different educational institutions in the world, being a learning tool that improves skills and academic results; such as the development of the IMELS Android application, using MySql and the Java programming language, added to this the implementation of Moodle (web learning platform) [20], thus allowing free access at any time and place, see Figure 11. It is demonstrated that its implementation contributes to inclusive education through a specific game for children with dyslexia called FORDYS-VAR [13] Figure 12 although it is in the beta phase, detecting errors to solve them, and children with dyslexia has no complications in understanding the game, they managed to obtain an influence and understanding of the high impact on these children. As a result, it shows that Virtual Reality technology for the education of children with dyslexia can be effective and easy to use.…”
Section: Gamesmentioning
confidence: 99%
See 1 more Smart Citation